Between the sampling distribution of CVc and CVr for exponential samples from simulated and real data. - Maarof, Fauziah; Ahmad, Aimi Athirah; Mohamed, Shamsiah
First part of this paper reviews the results, obtained via simulation, of the properties of the sampling distribution of the conventional coefficient of variation, CVc and that of a robust coefficient of variation based on the mean absolute deviation (MAD), CVr for samples from exponential distribution. The properties of emphasis are symmetricity, peakedness and spread. Second part of the paper presents exemplification on the preservation of the observed properties in exponentially distributed engineering relayed real data sets. Also presented are observations made on the effect of stipulated presence of outliers in the real data sets used.